Accelerated versus standard Ponseti cast in the management of idiopathic congenital talipes equinovarus at a tertiary care centre in North India: a comparative study - Singh, Suraydev Aman; Bahl, Saransh; Khan, Ifzal Ahmed; Khajuria, Ankita; Mahajan, Neeraj; Gupta, Sanjeev (International Journal of Research in Orthopaedics, 2023)
Background: Congenital talipes equinovarus varus (CTEV) is one of the most common congenital anomalies of foot and ankle. With a male dominance pattern, this deformity is bilateral in around 50% cases. It is characterized across varying degrees and severity of components manifesting with: forefoot adductus, midfoot cavus, hindfoot varus and hindfoot equinus. Severity is accessed using Pirani score (0 to 6). Insights into the basic patho-anatomy of this complex 3-dimensional deformity has helped to correct it using the method given by Ignacio Ponseti, a Spanish orthopedician, in which serial manipulations of foot are done and weekly casts are applied, followed by a tendoachilles tenotomy in selected cases to correct the equinus component which is then followed by splintage of the feet in foot-ankle orthosis initially for 23 hours day for 3 months and then 12 hours a day for 3 years. Parental counselling regarding the importance of compliance with maintenance braces remains the most important component of treatment. Methods: This was a double blinded randomized prospective study including 40 patients with 61 feet of only idiopathic clubfoot, conducted in the department of orthopaedics, government medical college, Jammu over a period of 01 year. Results: The mean days of plaster duration in accelerated casting group was 18.45 days as compared to 47.25 days in standard casting group (statistically significant, p<0.05). Also, Pirani score at the end of last follow up was comparable in both the groups. Tenotomy rate was slightly higher in accelerated casting group (89.5%) as compared to standard group (85.7%) which may be attributed to higher initial Pirani score in former (5.5) as compared to later (5.0). Conclusions: The clubfoot in developing countries has social stigma, the early and the promising result of the accelerated method of Ponseti casting has a dramatic impact on both parents and the treating orthopaedician. The accelerated Ponseti casting has remarkably reduced the overall duration of the treatment of Ponseti casting without any complication.